1998
DOI: 10.2307/3434178
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Human Osteoblast Cells to the Tumorigenic Phenotype by Depleted Uranium-Uranyl Chloride

Abstract: Depleted uranium (DU) is a dense heavy metal used primarily in military applications. Although the health effects of occupational uranium exposure are well known, limited data enxst rding the long-term health effects of internaized DU in humans. We established an in viuro cellular model to study DU exposure. Microdosimetric assessment, determined using a Monte Carlo computer simulation based on measured intracelular and etacelular u m levels, showed that few (0.0014%) cell nuldei were hit by alph partidles. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
1
35
0
Order By: Relevance
“…The presence of uranium in the body can cause damage to the kidneys, leading to nephritis (Tutu et al, 2005). In addition, the genotoxic effect has been studied (Miller et al, 1998) and detailed description of the toxicological effects of depleted uranium can be found elsewhere (Patočka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of uranium in the body can cause damage to the kidneys, leading to nephritis (Tutu et al, 2005). In addition, the genotoxic effect has been studied (Miller et al, 1998) and detailed description of the toxicological effects of depleted uranium can be found elsewhere (Patočka et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro exposure of different cell types to DU increased the frequency of MN (Miller et al 2001a(Miller et al , b, 2003 and the phenotype transformation rate of the cells (Miller et al 1998). Yazzie et al (2003) reported that the inhaling of DU by rats can produce breaks and oxidative damage to the nitrogenated bases of the DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Chinese hamster ovary (CHO) cells exposed to uranyl nitrate (UO 2 2+ ) found an increased frequency of micronuclei, SCE and CAs (Lin et al 1993). In a human osteoblast (HOS) cell line, increased SCE and an increase in transformation to a tumorigenic phenotype was seen in DU exposed cells in culture (Miller et al 1998a). Miller et al (1998b) also showed increased urine mutagenicity in TA98 and AMES II (TA 7001-7006) in DU-implanted animals.…”
Section: Genotoxicitymentioning
confidence: 95%